The Effect of Halal Labels on Purchasing Decisions for Wardah Cosmetics of Students Islamic Building School of Jagad 'Alimussirry - Mukharromah, Gabrielle Lailatul; Rahmatika, Resty (http://jagadalimussirry.com/, 2020)
Abstract. The purpose of this study was to determine the effect of the halal label on purchasing decisions for students of the Jagad 'Alimussirry Islamic Boarding School. The research method used is quantitative research. The sample in this study were 47 respondents, using a purposive sampling technique. The data analysis used is simple linear regression. The results showed that the halal label variable had a significant effect on the purchasing decision for Wardah cosmetics with a significant value of 0.000. The contribution of the independent variable, namely the halal label, affects the dependent variable, namely the purchase decision by 39.3%. While the remaining 60.7% is influenced by other variables not examined in this study.